Dampak Implementasi Core Values BerAKHLAK dan Employer Branding Aparatur Sipil Negara terhadap Kualitas Pelayanan Publik di BKPSDM Kabupaten Kebumen - Marhati Dwi Cahyani; Sri Wahyuningsih (JURNAL ILMIAH EDUNOMIKA, 2026)
Optimal public service is a key indicator of successful bureaucratic reform. To achieve this, the government promotes the internalization of BerAKHLAK core values and strengthening the employer branding of civil servants (ASN) to fostor a professional work culture. However, there remains a gap between ideal values and their implementation in the field, affecting public perception of service quality. This study aims to analyze the influence of BerAKHLAK core values and ASN employer branding on the quality of public services. A quantitative approach was used, with a survey of 122 respondents selected through purposive sampling. Data were using Partial Least Squares-Structural Equation Modeling (PLS-SEM) with SmartPLS version 4 software. The results show that BerAKHLAK core values do not have a significant effect on public service quality, while ASN employer branding has a positive and significant effect. These findings indicate that a strong employer brand contributes more effectively to improving service quality then merely applying of organizational values. Therefore, it is recommended that BKPSDM strengthen the internalization of BerAKHLAK values and develop ASN employer branding in a structured and sustainable manner. Keywords: Core Values BerAKHLAK; Employer Branding; Public Service Quality; Kebumen Regency